2016
DOI: 10.1017/jns.2016.6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of long-term use of oral nutritional supplement on nutritional adequacy, dietary diversity, food intake and growth of Filipino preschool children

Abstract: Nutrient deficiencies during childhood have adverse effects on child growth and health. In a single-arm 48-week long-term intervention, we previously reported the efficacy of oral nutritional supplementation (ONS) and dietary counselling on catch-up growth and growth maintenance in nutritionally at-risk Filipino children. The present analysis was done to assess the contributing effects of ONS to nutritional adequacy, dietary diversity, food intake and longitudinal growth. ONS (450 ml) was consumed daily provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
3
6
0
2
Order By: Relevance
“…Twelve weeks consumption of fortified milk group increased the height of preschool children by 1.40 ± 0.04 cm, weight by 1.35 ± 0.04 kg, body mass index of 0.96 ± 0.04 kg/m 2 , and mid-upper arm circumference of 0.66 ± 0.01 cm. Findings in the present study are consistent with studies on the effect of milk supplementation on anthropometric status of children [ 11 , 16 , 20 ]. The average increase in height of a preschool child is about 2-3 inches a year or around 0.17–0.25 inch (0.43–0.64 cm) a month, while the average weight gain is about 5-6 pounds per year or 0.19–0.23 kg per month [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Twelve weeks consumption of fortified milk group increased the height of preschool children by 1.40 ± 0.04 cm, weight by 1.35 ± 0.04 kg, body mass index of 0.96 ± 0.04 kg/m 2 , and mid-upper arm circumference of 0.66 ± 0.01 cm. Findings in the present study are consistent with studies on the effect of milk supplementation on anthropometric status of children [ 11 , 16 , 20 ]. The average increase in height of a preschool child is about 2-3 inches a year or around 0.17–0.25 inch (0.43–0.64 cm) a month, while the average weight gain is about 5-6 pounds per year or 0.19–0.23 kg per month [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
“…Only 27.6% of children aged 6 months to 5 years drink milk [ 1 ]. Most Filipino children have low energy and nutrient intakes [ 20 ] which may have long term effects not only in their anthropometric measurements but also in their psychomotor abilities [ 10 – 16 ]. Identifying viable means of providing significant nutrients therefore may be of high importance.…”
Section: Introductionmentioning
confidence: 99%
“…Picky eaters (aged 3–5 years) with faltering growth who were randomized to receive 3-month oral nutritional supplementation had significantly greater increases in weight and height than non-supplemented controls, and developed proportionally fewer upper respiratory tract infections ( 35 ). Long-standing oral nutritional supplementation helped promote nutritional adequacy and growth in Filipino children who were at risk of nutritional deficiency ( 36 ). The results showed that long-term use of oral nutritional supplement improved food diversity and promoted adequate intake of nutrients that were inadequate in Filipino children’s diets without interfering the intake of normal family foods.…”
Section: Discussionmentioning
confidence: 99%
“…Past work has found that caloric supplementation leads to accelerated height in severely underweight children. 42,43 Therefore, it is possible that only children experiencing marked weight loss with CNS stimulants, which is relatively uncommon, 13 may exhibit increased height velocity with caloric supplementation.…”
Section: Discussionmentioning
confidence: 99%